2007
DOI: 10.1007/s10755-007-9049-5
|View full text |Cite
|
Sign up to set email alerts
|

A Feminist Perspective on Parental Leave Policies

Abstract: This article focuses on the ways that three feminist theories-liberal feminism, cultural feminism, and feminist poststructuralism-might be used to craft parental leave policies. After examining each theory in detail, the article concludes by offering one example of an ideal parental leave policy that combines the best features of each theory to produce a policy that is responsive to faculty needs and works to change gender roles. Often faculty and administrators implement policies without truly thinking throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 14 publications
1
24
1
Order By: Relevance
“…First, a positive departmental climate is associated with faculty success, especially for female faculty with children (Campbell & O’Meara, 2014; Mason & Ekman, 2007; Mason & Goulden, 2004; O’Meara & Campbell, 2011). Second, senior leadership (e.g., president, deans) are responsible for ensuring that department chairs are on board with promoting institutional work–family policies, given that chairs are critical in enabling faculty to balance their work and family roles (Sallee, 2008). Department chairs also matter because early tenure-line faculty have limited information about how to best navigate the department culture and attain tenure (Lester, 2013); chairs can clarify the rules of the game to assist female faculty members in becoming successful (Campbell & O’Meara, 2014; Trower & Chait, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a positive departmental climate is associated with faculty success, especially for female faculty with children (Campbell & O’Meara, 2014; Mason & Ekman, 2007; Mason & Goulden, 2004; O’Meara & Campbell, 2011). Second, senior leadership (e.g., president, deans) are responsible for ensuring that department chairs are on board with promoting institutional work–family policies, given that chairs are critical in enabling faculty to balance their work and family roles (Sallee, 2008). Department chairs also matter because early tenure-line faculty have limited information about how to best navigate the department culture and attain tenure (Lester, 2013); chairs can clarify the rules of the game to assist female faculty members in becoming successful (Campbell & O’Meara, 2014; Trower & Chait, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Several work-family scholars argued for more equitable work-family policies for both male and female academics (Colbeck & Drago, 2005;Lundquist et al, 2012). They suggested that policies should recognize that female faculty members face physical demands on their bodies due to childbirth in addition to demands of caregiving, while also making it possible for faculty fathers to equally engage in caregiving (Lundquist et al, 2012;O'Meara & Campbell, 2011;Sallee, 2008Sallee, , 2013. To ensure that family-friendly policies are used for their intended purpose and not as a way of increasing productivity (as during a sabbatical), scholars have suggested that productivity during family leave should not count in tenure evaluations (e.g., Colbeck & Drago, 2005).…”
Section: Literature On Institutional Work-family Policies and Practicementioning
confidence: 99%
“…Maher et al (2004) found that many women encountered one or more major obstacles that delayed progress, including: child-care responsibilities; disruption of family life due to death or divorce, and/or the inability to secure stable funding (see also Dey and Hill, 2008;Sallee, 2008). Finally, women reported less success in securing research experiences that aided dissertation efforts as well as a lack of confidence in their ability to navigate implicit institutional mores.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Supported by findings from Salee (2008), family leave policies appeared to greatly impact the changes in family dynamics. Two of the mothers expressed that due to paternal leave their husbands had been able to take on more of the childcare responsibilities in the beginning weeks, helping to establish the fathers' connection to their children and their responsibilities within the household.…”
Section: Mamas' Solutions For Mamasmentioning
confidence: 91%